2009
DOI: 10.4028/www.scientific.net/msf.628-629.245
|View full text |Cite
|
Sign up to set email alerts
|

Research on Reliability Allocation of Direct-Drive Hobbing Machine

Abstract: In the early design phase of direct-drive hobbing machine, to allocate the reliability index scientifically and reasonably without the related reliability data, fuzzy analytic hierarchy process (fuzzy AHP) is used to allocate the reliability index of the main system units of direct-drive hobbing machine. This method is an effect way for multi-factor decision, which can consider the influence of the factors of every hierarchy on the machine maximatily and calculate the influence weights of the factors of every … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…The studies of the authors Zahedi and Ashrafi (1991), Zhang and Liao (2009), Cheng et al (2014), Chatterjee et al (2015), Subhashis et al (2015), Chen et al (2016), Di Bona et al (2016, Li et al (2016), Ma et al (2016) and Di Bona and Forcina (2017) can be given as example studies of using AHP in reliability allocation process. Decision making trial and evaluation laboratory (DEMATEL) method besides the AHP is another preferred MCDM method in the literature.…”
Section: Literature Review: Methodological Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…The studies of the authors Zahedi and Ashrafi (1991), Zhang and Liao (2009), Cheng et al (2014), Chatterjee et al (2015), Subhashis et al (2015), Chen et al (2016), Di Bona et al (2016, Li et al (2016), Ma et al (2016) and Di Bona and Forcina (2017) can be given as example studies of using AHP in reliability allocation process. Decision making trial and evaluation laboratory (DEMATEL) method besides the AHP is another preferred MCDM method in the literature.…”
Section: Literature Review: Methodological Perspectivementioning
confidence: 99%
“…In the literature review, it is found that AHP mostly utilized MCDM method. The studies of the authors Zahedi and Ashrafi, 12 Zhang and Liao, 13 Cheng et al, 14 Chatterjee et al, 15 Li et al, 16 Ma et al, 17 Subhashis et al, 15 Chen et al, 18 Di Bona et al, 19 Di Bona and Forcina, 20 and Di Bona et al 21…”
Section: Literature Review: Methodological Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…The studies of the authors Zahedi and Ashrafi (1991), Zhang and Liao (2009) Apart from the MCDM methods aforementioned, multi objective optimization methods (Malec, 1977;Sakawa, 1978;Cho et al, 1987;Bari et al, 1985;Rao and Dhingra, 1992;Liu & Li, 2003;Zavala, 2005;Zhao et al, 2005;Zio and Bazzo, 2011;Zhang and Wu, 2012;Zio and Bazzo, 2012;Sangeetha et al, 2014;Falcone et al, 2018), integrated factors method (Falcone, Silvestri and Di Bona, 2003), genetic algorithm method (Yang et al, 1999;Lu et al, 2004;Kumral, 2005;Zia and Coit, 2006;Xu et al, 2007;Liu et al, 2007;Liao 2009;, Markov Chain (Ke-Rong et al, 2001), Bayesian network (Qian et al, 2012;Ma et al, 2016;), FMEA (Chang et al, 2013;Sadeghi et al, 2014;Wang et al, 2016), Monte Carlo (Fan et al, 2014;), critical flow method (Silvestri et al, 2015) and data envelopment analysis method (Zhang & Huang, 2016) are other important methods used in the literature to minimize the shortcomings of traditional reliability allocation methods.…”
Section: Literature Review: Methodological Perspectivementioning
confidence: 99%
“…Ivanovic (2000) applied the reliability allocation problem for a new vehicle design. Similarly, Zhang and Liao (2009) also studied the problem of reliability configuration in view of a mechanical components/systems. Authors applied it for direct drive hobbing machine.…”
Section: Optimization Of Fleet System Reliability Designmentioning
confidence: 99%